Crystal structure and catalytic properties of a vanadium complex cis-[VO2(Him-py)(im-py)]2·3H2O. Issue 11 (3rd June 2019) - Sun, Meng; Zhang, Shaowei; Zhang, Jie; Xia, Wen; Chen, Jialiang; Yu, Xianyong
Abstract: The coordination behavior of Him-py (2-(1H-imidazol-2-yl)pyridine) toward vanadium has been explored. The six-coordinate complex, cis -[VO2 (Him-py)(im-py)]2 ·3H2 O (1 ), was synthesized by the coordination reaction of NH4 VO3 and Him-py in the aqueous methanol solution, which was characterized by single-crystal X-ray technology. It belongs to the monoclinic space group P 21 /n with a  = 8.0756(6), b  = 19.3531(15), c  = 11.4433(8), β  = 106.905(2), V  = 1711.2(2), and Z  = 2. The crystal structure shows that the six-coordinate vanadium is bonded to two cis -oxido ligands and two bidentate ligands, Him-py and im-py. Interestingly, when crystals of1 were immersed in H2 O2, a peroxovanadium compound, (H2 im-py)[OV(O2 )2 (Him-py)] (2 ), was obtained, which crystallizes in the orthorhombic space group Fdd2 with a  = 22.600(2), b  = 22.7259(13), c  = 18.0146(11), V  = 9252.4(12), and Z  = 16, and consists of a seven-coordinate peroxovanadate(V) ion, one Him-py and one H2 im-py ligand. Moreover, we also studied the catalytic activity of1 in the oxidative bromination of phenol/aniline-like compounds towards mimicking bromoperoxidase reactivity. Abstract :